2015
DOI: 10.7150/jca.9558
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological Correlation of β-Catenin and Telomere Dysfunction in Head and Neck Squamous Cell Carcinoma Patients

Abstract: Background: Tumorigenesis is a complex process of accumulated alteration in function of multiple genes and pathways. Wnt signalling pathway is involved in various differentiation events during embryonic development and is conserved in various species.Objective: A multicentre collaborative initiative is undertaken to study the occurrence, prognosis and molecular mechanism of HNSCC (Head and Neck Squamous Cell Carcinoma) which is highly prevalent in eastern parts of India. From a large cohort of HNSCC tissue rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Beside hematological malignancies, a contribution of dysregulated Wnt signaling was also demonstrated for oral squamous cell cancer (OSCC) and aberrant accumulation of β-cat seems to support invasion and migration of OSCC cells, at least in vitro (see [11] and references therein). In accordance, Padhi et al reported of a correlation between β-cat expression and poor prognosis in head and neck cancer [12] in vivo . This is supported by the very recent finding that inactivation of several Wnt inhibitors through methylation is frequently found in oral cancer, correlating with a shorter survival [13].…”
Section: Introductionsupporting
confidence: 76%
“…Beside hematological malignancies, a contribution of dysregulated Wnt signaling was also demonstrated for oral squamous cell cancer (OSCC) and aberrant accumulation of β-cat seems to support invasion and migration of OSCC cells, at least in vitro (see [11] and references therein). In accordance, Padhi et al reported of a correlation between β-cat expression and poor prognosis in head and neck cancer [12] in vivo . This is supported by the very recent finding that inactivation of several Wnt inhibitors through methylation is frequently found in oral cancer, correlating with a shorter survival [13].…”
Section: Introductionsupporting
confidence: 76%
“…Previously we reported importance of β-catenin in prognosis of oral cancer and its overexpression in clonospheres along with hTERT and TRF2 [20,22]. In the present study, we observed a significant overexpression of β-catenin, TRF2 and hTERT at 40µM concentration and low expression was observed at 80µM concentrations compared to the untreated control (p<0.001) in parental HCT-116 (Fig 2e).…”
Section: Discussionsupporting
confidence: 62%
“…A significant population of cells was observed to efflux Hoechst 33342 dye when treated with increasing concentration of Bleomycin (20,40, 60, 80 μM) (Fig 1a and 1b). This small subpopulation of cells called Side Population (SP) increased with increasing concentration and then stabilized to a uniform percentage at higher concentrations.…”
Section: Prevalence Of a Side-population Of Cells With Stem Cell Likementioning
confidence: 97%
See 2 more Smart Citations